Łacina: powrót do przyszłości? Kilka refleksji nad łaciną i kwestiami literackimi w epoce digitalizacji - Vogt-Spira, Gregor (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
Vogt-Spira Gregor, Latin: Back to the Future? Some Reflections on Latin and Literacy in the Digital Age (Łacina: powrót do przyszłości? Kilka refleksji nad łaciną i kwestiami literackimi w epoce digitalizacji). This paper argues that Latin meets the challenges of this day and age so that its preservation actually has a well-founded place within European countries and societies. The argumentation starts by the observation that Latin gathers a number of additional values as an alterity training, a cognitive training, a linguistic training or a socially integrative effect, values, which are remarkably not bound to a specific culture. Above all, digitization and the modern cybernetic world is seen as a central challenge, digitization with its enormous quantitative increase in reading and writing activity also transforms the user profile in a way that complements it, a factor to which educational institutions have yet to come up with a conclusive response. Referring to this development, Latin has the particular significance of imparting the standards of an elaborate written form into the composition and decoding of texts. Furthermore, Latinity itself is considered to be one of the key factors that have shaped modern-day Europe, and the later Latin-language literature is seen to be a comprehensive component of each country’s respective national literature and culture. To conclude, the ancient European custom is brought into focus that, practically, antiquity serves as a vehicle for legitimizing modernization.